Self-powered solar tracking system part 1: system modeling and hardware selections - Abdul Muthalif, Asan Gani; Hafiz, Dzairul; Shafiq, Haris (IIUM Press, 2011)
Solar power is an alternative technology that will hopefully leads us away from petroleum dependant energy sources. The main issue regarding conventional solar panel is about its efficiencies of power absorption. Researches had been conducted and found out that the maximum power absorption happen when the panel is normal to the solar rays [1]. To orient the solar panel according to the sun’s position can be achieved by implementing motors and actuators in the system. The implementation of motors and actuators will create a mechanism to control the orientation of the panel. There are quite numbers of solar tracker system nowadays that are being used widely. There are two types of solar tracker that is single axis and dual axis tracker. Basically, in order to orient the panel according to the sun position, the study of the elevation angle of the sun is necessary. This angle differs with its location. For accommodating this matter, dual axis solar tracking system should be more appropriate [2]. This chapter discusses the system modeling and hardware selection for the two axis solar tracker.